2017
DOI: 10.3389/fendo.2017.00355
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Exocytosis by Vesicle Fusion in Neuroendocrine Cells

Abstract: MicroRNAs (miRNAs) are short non-coding RNAs that posttranscriptionally regulate gene expression inside the cell. Extracellular circulating miRNAs are also observed outside the cell, but their origin is poorly understood. Recently, miRNA has been shown to be exocytosed by vesicle fusion; this observation demonstrates that vesicle-free miRNAs are secreted from neuroendocrine cells, in a manner similar to hormone secretion. miRNAs are stored in large dense-core vesicles together with catecholamines, then release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…This finding implies that spontaneous electric activity of neurons was important for miRNA secretion. Electric activity of neurons is known to increase exocytosis (Chivet et al, ; Park, ), and also facilitate opening of voltage‐gated channel proteins that might also directly and/or indirectly contribute to the release of ECmiRNAs. This is quite an interesting and important finding, which will be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This finding implies that spontaneous electric activity of neurons was important for miRNA secretion. Electric activity of neurons is known to increase exocytosis (Chivet et al, ; Park, ), and also facilitate opening of voltage‐gated channel proteins that might also directly and/or indirectly contribute to the release of ECmiRNAs. This is quite an interesting and important finding, which will be further investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…DCVs in the CNS are primarily peptidergic vesicles (LDCVs), packaging neuropeptides and peptide hormones [117, 118]. In addition, LDCVs may co-store monoamines, neurotrophic factors, ATP, miRNAs as well as pre-assembled components that need to be transferred to synaptic active zones [119, 120]. Neuropeptides are the most diverse and most numerous signaling molecules in the brain, acting as neurotransmitters, neuromodulators and neurohormones.…”
Section: εVs In the Cnsmentioning
confidence: 99%
“…Of note, neuropeptides that act as neuromodulators may activate receptors all along the target cells [118]. LDCVs often contain multiple neuropeptides, the latter being sorted into different LDCVs in the same cells [119, 121, 122]. In addition, LDCVs are enriched with miRNAs (∼60% of LDCV RNA content) [119], which are released via SNARE-mediated exocytosis in a Ca ++ -dependent manner [122].…”
Section: εVs In the Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 miRNAs are transported out from cells mainly by exocytosis, and they are either encapsulated in or free from vesicles for cell-cell communication. 9 A growing body of evidence demonstrates the promising utility of circulating miRNAs as biomarkers of noncommunicable diseases, but their pre-analytical processing and detection still suffer from several challenges. 10 Despite the good number of scientific publications about issues and improvements in certain pre-analytical parts for the study of circulating miRNAs, such as sample processing and circulating miRNA extraction, no study has reported the suitability of utilizing circulating miRNA extracts with low purity and yield in detecting miRNA using quantitative realtime polymerase chain reaction (qPCR).…”
Section: Makara J Health Resmentioning
confidence: 99%